Effectiveness Of The Core Activation And Rehabilitation Exercises For Knee Osteoarthritis - Program (CARE -KOA©) Among Patients Diagnosed With Knee Osteoarthritis. [version 4; peer review: 2 approved] - Saurabh Mehta; Ajit R. Mahale; Dias Tina Thomas; Prajwal Prabhudev Mane; Atmananda S Hegde; Charu Eapen (F1000Research)
Background Knee osteoarthritis (KOA) is a prevalent condition. Recent research highlights the role of kinetic chain and core muscle involvement in disease progression, yet evidence for structured core activation protocols such as CARE-KOA© remains limited.This study addresses this gap by evaluating the effectiveness of CARE-KOA©, which specifically targets proximal stability and biomechanical deficits in KOA, aiming to enhance pain, function, and core endurance beyond conventional approaches. Methods This prospective single-group pre-post study assessed the effect of a Participants underwent a 4-week CARE-KOA© regimen (12 supervised sessions, each including a 10-minute warm-up and core-focused exercises). Pre- and post-intervention assessments included pain (Visual Analog Scale, VAS), patient-reported outcomes (Knee Injury and Osteoarthritis Outcome Score, KOOS), physical function tests (30-second sit-to-stand, 40-meter fast-paced walk, stair climb, timed up-and-go), and knee muscle strength and core endurance. Statistical analysis was performed using non-parametric tests in JAMOVI. Results Significant improvements were observed in pain at rest (mean change: 1.13 cm, p = 0.0006, d = 1.07) and during activity (mean change: 2.46 cm, p = 0.000001, d = 1.76), patient-reported outcomes (KOOS Pain: p = 0.00003, d = -0.83; KOOS ADL: p = 0.0000009, d = -1.19), and core endurance (p = 0.027, d = 0.21). Physical function tests also improved (stair climb: p = 0.031, d = 0.34; timed up-and-go: p = 0.006, d = 0.13). Muscle strength gains were significant in flexors of the unaffected knee and extensors of the affected knee (p < 0.05), while other muscle groups showed no significant change. Conclusion The CARE-KOA© program led to clinically meaningful improvements in pain, function, and core endurance, highlighting the value of core activation strategies in KOA management. Future research with larger samples and longer follow-up is warranted to confirm these benefits and optimize exercise protocols. Study Trial Registration CTRI/2023/07/05480 on 05/07/2024 https://ctri.nic.in/Clinicaltrials/regtrial.php?modid=1&compid=19&EncHid=69416.70327 Copy right registration: L – 158197/2024